2015
DOI: 10.2174/1874836801509010303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Current Situation and Development Trend of Construction Worker’s Occupational Mobility

Abstract: Occupational mobility is one of the hotspots in academic research. The construction worker’s occupational mobility is the key element of affecting the healthy and sustainable development of construction industry in China. Based on domestic and foreign occupational mobility literature, this paper analyze the regional distribution, classic literatures and hotspots about construction worker’s occupational mobility, by Citation Network, Keyword Co-Occurrence and other bibliometrics and qualitative tools. It sort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Many scholars have conducted theoretical and empirical research on the issue, primarily on the fields of medical care (Desousa and Murrells, 2005;McHale et al, 2019), the education industry (Connelly et al, 2017;Pienaar and Zhao, 2017;Ryazanova and McNamara, 2019) and relevant government industries (Mei and Wang, 2017;Shah, 2011). As a highly mobile sector (Sun et al, 2015), the human resource development in a construction organization is a worthy research field (Nkomo et al, 2018), and the promotion of the construction industry deserves attention. However, few studies are available on the career promotion of construction industry, and their research objects are all construction professionals with higher education (Rosa et al, 2017;Simmons et al, 2018).…”
Section: Career Promotionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many scholars have conducted theoretical and empirical research on the issue, primarily on the fields of medical care (Desousa and Murrells, 2005;McHale et al, 2019), the education industry (Connelly et al, 2017;Pienaar and Zhao, 2017;Ryazanova and McNamara, 2019) and relevant government industries (Mei and Wang, 2017;Shah, 2011). As a highly mobile sector (Sun et al, 2015), the human resource development in a construction organization is a worthy research field (Nkomo et al, 2018), and the promotion of the construction industry deserves attention. However, few studies are available on the career promotion of construction industry, and their research objects are all construction professionals with higher education (Rosa et al, 2017;Simmons et al, 2018).…”
Section: Career Promotionmentioning
confidence: 99%
“…Many people are prejudiced against the occupation of construction workers and think that the latter are engaged in low social-economic status work (Sing et al, 2017). The abnormal occupational mobility of construction workers is also very serious (Sun et al, 2015), and the space for career promotion is small (Wang et al, 2015), thereby resulting in a severe brain drain in the construction industry and causing the construction enterprises to lack skilled workers for a long time (Barbosa et al, 2017), a situation which is not conducive to the efficient and healthy development of the said industry. Weng and McElroy (2012) revealed that according to the expectation theory (Porter and Steers, 1973), career promotion, as one of the four factors affecting career growth, can make employees find career development opportunities (Dharmaratne and Gunasekara, 2017), promote employees' organizational commitment, make them more loyal and dedicated, and reduce employees' turnover intention.…”
Section: Career Promotionmentioning
confidence: 99%
See 3 more Smart Citations